Off-Label Use of Dalbavancin for Sequential Treatment of Spondylodiscitis by Methicillin-Resistant Staphylococcus aureus: A Retrospective Single-Centre Experience - Maria Mazzitelli; Milo Gatti; Vincenzo Scaglione; Daniele Mengato; Marco Trevenzoli; Andrea Sattin; Federico Pea; Anna Maria Cattelan (MDPI AG, 2022)
Background: Our aim was to describe the clinical outcome and safety of the sequential treatment with off-label dalbavancin in patients with spondylodiscitis that is caused by methicillin-resistant Staphylococcus aureus (MRSA). Methods: We retrospectively included all patients >18 years of age with spondylodiscitis that is caused by MRSA that was treated with dalbavancin from January 2018-January 2021, recording the instances of clinical cure/failure, adverse events, and the need to be re-hospitalized after the initiation of dalbavancin. In 2/15 patients, we performed therapeutic drug monitoring (TDM) for dalbavancin. Results: We included 15 patients, 53.3% of them were females, with a median age of 67.9 years (57.4-78.5); 100% patients reported back pain, while a fever was present only in 2/15 cases. The spondylodiscitis was localized in 86.6% cases at the lumbar level. A median of a 2-week in-hospital intravenous vancomycin was followed by dalbavancin with a median duration of 12 weeks (12-16). All patients reported a clinical cure, except for a woman who is still on a suppressive treatment. No patient needed to be re-hospitalized, access to emergency department, or experienced adverse events. The TDM for dalbavancin showed that more than 90% of the determinations were above the pharmacodynamic target against staphylococci. Conclusions: The results from our unique, even if it was small, cohort demonstrated that dalbavancin can be a safe/effective option as a sequential treatment in patients with serious infections requiring prolonged antibiotic therapy, such as spondylodiscitis.